Correlation of Award Giving to Athletes’ Achievements in The Academic Field at Junior High School 1 Baleendah - Muhammad Rafli Fauzy; Nuryadi; Tri Martini (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
The purpose of this study was to determine the correlation between the awarding of academic achievement awards to student athletes and their academic performance. The researcher used a quantitative approach with a questionnaire survey that was correlated with the student athletes’ report card grades. The sample in this study consisted of 146 student athletes at Junior High School 1 Baleendah. The results of the study indicate that there is a positive and significant correlation between the awarding of scholarships and academic performance. Scholarships, pocket money, and medals awarded by the organizers of competitions can improve the quality of student athletes’ learning at school, enabling their academic performance to compete with that of regular students, even though competitions do not hinder their learning. This study indicates that being both a student and an athlete does not hinder students from achieving academic success but rather serves as motivation for student athletes to strive harder for academic achievements. The implications of this study are that the athlete class program should be implemented more widely, especially in Bandung Regency, to encourage student athletes to be more active in academic pursuits so they can achieve both academic and sports achievements, and for schools to provide adequate facilities for student athletes.